Silicon-based composite material and preparation method thereof
By using silicon-based composite materials with carbon-covered outer layer, carbon-filled layer and secondary particle structures of multiple primary particles, the low first-time Coulomb efficiency and high cyclic expansion rate of silicon oxygen negative electrode materials in lithium-ion batteries are solved. and gas production issues have achieved improvements in high-rate performance and stable processing performance.
Patent Information
- Application Number
- CN202311103196.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-08-29
- Publication Date
- 2025-02-11
- Estimated Expiration
- 2043-08-29
AI Technical Summary
The existing silicon oxygen negative electrode materials have low first-time Coulomb efficiency, high cyclic expansion rate and gas production problems in lithium-ion batteries, which are difficult to meet the needs of new energy vehicles for high-rate performance and stable processing performance.
The silicon-based composite material with a carbon-coated outer layer, a carbon-filled layer and a secondary particle structure of multiple primary particles is prepared by solid-phase mixing and vapor-phase cladding technology to ensure that the minimum size of the carbon-filled layer reaches more than 0.5μm. Enhanced conductivity and waterproofing.
The first Coulomb efficiency and rate performance of silicon-based composite materials are significantly improved, the gas production problem after prelithiation is avoided, and the processing performance of the slurry is improved.
Smart Images

Figure CN117174857B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of material preparation, and in particular to a silicon-based composite material and a preparation method thereof. Background Art
[0002] At present, lithium-ion batteries mainly use graphite as the negative electrode material. With the rapid development of new energy vehicles, the low gram capacity of graphite negative electrodes cannot meet the current usage needs. In pursuit of higher gram capacity, silicon negative electrodes are considered to be the first choice for the next generation of lithium-ion battery negative electrode materials due to their extremely high gram capacity (4200mAh / g) and moderate platform voltage.
[0003] Silicon negative electrode materials can be roughly divided into two series, silicon-carbon negative electrode materials and silicon-oxygen negative electrode materials. Silicon-carbon negative electrode materials are mainly composed of nano-silicon and coated carbon. Due to the huge volume expansion of silicon during lithium insertion, silicon-carbon negative electrodes often show a higher cycle expansion rate. However, since the size of Si inside silicon-oxygen negative electrode materials is usually less than 20nm, the volume expansion rate brought about by them is greatly reduced, and during the lithium insertion process, Si is usually wrapped with lithium silicates, which can effectively prevent the pulverization of particles. Therefore, compared with silicon-carbon negative electrodes, silicon-oxygen negative electrodes have been commercially applied earlier and have been studied more.
[0004] Although silicon-oxygen anode has the advantage of lower cycle expansion compared to silicon-carbon anode, its own shortcomings cannot be ignored. One is that due to the large amount of oxygen in the elements that constitute the silicon-oxygen anode, a large amount of lithium silicate is often formed during the lithium insertion process, which consumes some reversible lithium ions, resulting in a low first coulomb efficiency (<80%) of silicon-oxygen anode materials. To solve this problem, researchers usually use the pre-lithiation method to modify it, which can effectively improve the first coulomb efficiency of the material to more than 90%. However, pre-lithiation will bring new problems. Since lithium silicate is soluble in water, its processing performance will deteriorate, mainly manifested in the increase of alkalinity of the slurry, the increase of residual alkali content, the decrease of slurry stability, the deterioration of the bonding effect of the binder, and the separation of the material from the current collector during the cycle. On the other hand, the dissolution of lithium silicate will cause the internal nano-Si to react with water during the homogenization process, resulting in the occurrence of gas production, and the formation of pores during the coating process, making the surface density of the electrode sheet uneven, which is easy to cause abnormal lithium precipitation.
[0005] In addition to solving the gas production problem after pre-lithiation, the high-rate charge and discharge performance of the material is also an urgent problem to be solved in the field of new energy vehicles. Since the electronic and ionic conductivity of silicon oxide materials themselves are extremely poor, they are generally carbon-coated. Although carbon coating alone can improve electronic conductivity, it cannot solve the problem of low ionic conductivity, so the rate performance is poor.
[0006] Therefore, developing a pre-lithium silicon-oxygen negative electrode material with high rate performance, no gas production, and good slurry processing performance has huge market value. Summary of the invention
[0007] In view of the above problems, the purpose of the present invention is to provide a silicon-based composite material and a preparation method thereof. The silicon-based composite material used in the present invention not only has a high first coulombic efficiency and rate performance, but also can effectively solve the gas production problem after pre-lithiation.
[0008] To achieve the above-mentioned object, the first aspect of the present invention provides a silicon-based composite material. The silicon-based composite material includes secondary particles, and the secondary particles include a carbon-coated outer layer, a carbon filling layer and a plurality of primary particles. The carbon-coated outer layer wraps the carbon filling layer, and a plurality of primary particles are filled in the carbon filling layer. The primary particles are silicon-based material particles containing lithium silicate, and the minimum size of the carbon filling layer between the primary particles and the carbon-coated outer layer is D, and D≥0.5μm.
[0009] The silicon-based composite material of the present invention has at least the following technical effects.
[0010] (1) The primary particles of the silicon-based composite material of the present invention are silicon-based material particles containing lithium silicate, which is equivalent to pre-lithiation of the silicon-based material. Therefore, the initial coulombic efficiency of the silicon-based composite material is relatively high.
[0011] (2) The silicon-based composite material of the present invention includes secondary particles. Compared with primary particles of the same particle size, the secondary particles are designed to have a larger surface area, and the insertion and extraction channels of lithium ions are increased. In addition, the secondary particles include a carbon-coated outer layer, a carbon filling layer, and a plurality of primary particles. The primary particles are coated with a plurality of carbon layers, which can not only inhibit the expansion of the silicon-based material, but also enhance the surface conductivity of the particles. Therefore, combined with the increase in the insertion and extraction channels and the increase in conductivity, the rate performance of the silicon-based composite material is also greatly improved.
[0012] (3) The minimum size of the carbon filling layer between the primary particles and the carbon coating outer layer is ≥0.5 μm, which means that the coating carbon layer outside the primary particles is thicker. This coating carbon layer has a strong waterproof penetration ability, which can prevent water from penetrating into the secondary particles and reacting with the primary particles, thereby avoiding the dissolution of lithium silicate in the primary particles, improving the high pH value, high residual alkali content and easy gas production of silicon-based materials after pre-lithiation, and ensuring the processing performance of the material.
[0013] In combination with the first aspect, the silicon-based composite material comprises a silicon-based core, a carbon-coated inner layer, a carbon filling layer and a carbon-coated outer layer. Optionally, there may be at least one (eg, one, two, three, etc.) carbon layer outside the carbon-coated outer layer.
[0014] In some embodiments, the silicon-based material particles include a silicon-based core and a carbon-coated inner layer encapsulating the silicon-based core, wherein the silicon-based core includes lithium silicate and nano-silicon.
[0015] In some embodiments, the lithium silicate includes at least Li2SiO3.
[0016] In some embodiments, the content of lithium in the silicon-based core is 5 wt.% to 15 wt.%.
[0017] In some embodiments, the size of the nano-silicon is 1 nm to 20 nm.
[0018] In some embodiments, the thickness of the carbon coating inner layer is from 20 nm to 100 nm.
[0019] In some embodiments, the carbon coating inner layer comprises 1 wt. % to 10 wt. % of the primary particle.
[0020] In some embodiments, the carbon filling layer is further filled with a plurality of conductive carbon particles.
[0021] In some embodiments, the conductive carbon particles comprise 0.5 wt. % to 10.0 wt. % of the carbon fill layer.
[0022] In some embodiments, the silicon-based composite material has a Dv50 of 5 μm to 15 μm.
[0023] In some embodiments, the particle size span of the silicon-based composite material is N, where N=(Dv90-Dv10) / Dv50, and N is between 0.9 and 1.4.
[0024] In some embodiments, the electrical conductivity of the silicon-based composite material is from 1.0 S / cm to 3.0 S / cm.
[0025] In some embodiments, the specific surface area of the silicon-based composite material is 0.7 m 2 / g to 1.5m 2 / g.
[0026] In some embodiments, the pH of the silicon-based composite material is between 10.5 and 11.5.
[0027] In some embodiments, the first coulombic efficiency of the silicon-based composite material is ≥ 90.0%.
[0028] In some embodiments, the first charge capacity of the silicon-based composite material is ≥ 1200 mAh / g.
[0029] In some embodiments, the first cycle reversible capacity of the silicon-based composite material is ≥ 459.0 mAh / g.
[0030] In some embodiments, the 0.2C reversible capacity of the silicon-based composite material is ≥ 444.0 mAh / g.
[0031] In some embodiments, the 0.2C reversible capacity retention rate of the silicon-based composite material is ≥ 96.0%.
[0032] In some embodiments, the 1.0C reversible capacity of the silicon-based composite material is ≥ 415.0 mAh / g.
[0033] In some embodiments, the 1.0C reversible capacity retention rate of the silicon-based composite material is ≥ 90.5%.
[0034] In some embodiments, the 2.0C reversible capacity of the silicon-based composite material is ≥ 370.0 mAh / g.
[0035] In some embodiments, the 2.0C reversible capacity retention rate of the silicon-based composite material is ≥ 80.0%.
[0036] In some embodiments, the 50-week reversible capacity retention rate of the silicon-based composite material is ≥ 91.0%.
[0037] In some embodiments, the full electrical expansion ratio of the silicon-based composite material is ≤45.0% after 50 cycles.
[0038] In some embodiments, the content of carbon in the silicon-based composite material is 10 wt.% to 30 wt.%.
[0039] In some embodiments, the content of LiOH in the silicon-based composite material is ≤ 0.1 wt. %.
[0040] In some embodiments, the content of Li2CO3 in the silicon-based composite material is ≤ 0.1 wt.%.
[0041] In some embodiments, the carbon coating outer layer has a thickness of 20 nm to 100 nm.
[0042] In some embodiments, the primary particles have a Dv50 of 0.5 μm to 5.0 μm.
[0043] In some embodiments, the carbon filler layer comprises 2 wt. % to 15 wt. % of the silicon-based composite material.
[0044] In some embodiments, 0.5 μm ≤ D ≤ 2.0 μm.
[0045] In some embodiments, the maximum dimension of the carbon filling layer between the primary particle and the carbon coating outer layer is H, 0.8 μm≤H≤1.8 μm;
[0046] In some embodiments, the maximum dimension of the carbon filling layer between the primary particles and the carbon coating outer layer is H, R=HD, R≤1.0.
[0047] The second aspect of the present invention provides a method for preparing a silicon-based composite material, comprising the steps of (I) preparing primary particles, (II) preparing a secondary particle precursor, and (III) preparing secondary particles.
[0048] Step (I) Preparation of primary particles: SiO x The powder is firstly carbon coated to obtain a primary particle precursor, the primary particle precursor is mixed with a lithium source, sintered and then post-processed to obtain a primary particle, <x<2。
[0049] Step (II) Preparation of secondary particle precursor: solid phase mixing and sieving of primary particles, binder and amorphous carbon source precursor to obtain secondary particle precursor. The maximum linear speed of the equipment used for solid phase mixing is 10m / s to 20m / s, and the solid phase mixing time is 0.5h to 4.0h.
[0050] Step (III) Preparation of secondary particles: subjecting the secondary particle precursor to a second carbon coating, the second carbon coating being a gas phase coating, and the temperature of the second carbon coating being not lower than the carbonization temperature of the binder and the amorphous carbon source precursor.
[0051] In combination with the second aspect, the coated carbon layer of the silicon-based composite material of the present invention includes at least the carbon coating in step (I), the carbonization of the binder and the amorphous carbon source in step (II), and the carbon coating in step (III). Optionally, a carbon coating layer may be further provided on the basis of the carbon coating in step (III). Optionally, at least one layer (e.g., one layer, two layers, three layers, etc.) of carbon layer may be additionally coated on this basis by means of carbon coating.
[0052] In combination with the second aspect, the present invention provides a silicon-based composite material prepared according to the aforementioned method for preparing the silicon-based composite material.
[0053] The method for preparing the silicon-based composite material of the present invention has at least the following technical effects.
[0054] 1. Use SiO x Carbon coating of powder can ensure the integrity of carbon coating, which is conducive to the stable performance of the primary particles obtained. x Powder pre-lithiation, that is, pre-lithiation of a single small particle, is relatively easy. The lithium source and SiO x There are many contact points, and lithium can easily migrate to SiO during pre-lithiation. x On the surface, the pre-lithiation process is fast, the degree is high, and the effect is good.
[0055] 2. The primary particles, binder and amorphous carbon precursor are solid-phase mixed. By controlling the maximum linear velocity at the end of the mixing equipment, the shear force is between the mixing and separation effects of the materials. At the same time, sufficient and appropriate mixing time is given to form an amorphous carbon precursor layer of sufficient thickness. Combined with gas phase coating, the minimum size of the carbon filling layer formed by carbonization of the binder and the amorphous carbon precursor can be ≥0.5μm, and the primary particles can be evenly coated.
[0056] In some embodiments, several conductive carbon particles are added together during the solid phase mixing.
[0057] In some embodiments, the conductive carbon particles include at least one of graphite, conductive carbon black, acetylene black, carbon nanotubes, and graphene.
[0058] In some embodiments, the mass ratio of the conductive carbon particles to the primary particles is 0.001 to 0.010:1.
[0059] In some embodiments, SiO x Powder block SiO x It can be obtained by crushing, grading and screening.
[0060] In some embodiments, SiO x The powder Dv50 is 1 μm to 10 μm.
[0061] In some embodiments, the first carbon coating is gas phase coating or solid phase coating.
[0062] In some embodiments, the carbon content of the first carbon coating is SiO x 0.5% to 5.0% of powder mass.
[0063] In some embodiments, the primary particle precursor and the lithium source are mixed in a solid phase and then sintered in a protective atmosphere.
[0064] In some embodiments, post-treatment includes cooling, washing, and drying in sequence.
[0065] In some embodiments, the lithium source includes one or more of lithium hydride, lithium hydroxide, lithium nitride, lithium amide, alkyl lithium, and metallic lithium.
[0066] In some embodiments, the lithium source comprises 5 wt. % to 20 wt. % of the mass of the primary particle precursor.
[0067] In some embodiments, the sintering temperature is 500°C to 750°C.
[0068] In some embodiments, the heating rate of sintering is 1° C. / s to 10° C. / s.
[0069] In some embodiments, the sintering holding time is 4 h to 24 h.
[0070] In some embodiments, the equipment used for solid phase mixing includes a mechanical fusion machine, a VC high-speed mixer, a planetary mixer, or a high shear mixer.
[0071] In some embodiments, the binder includes one or more of epoxy, polyurethane, and acrylate.
[0072] In some embodiments, the mass ratio of the binder to the primary particles is 0.005 to 0.200:1.
[0073] In some embodiments, the amorphous carbon source precursor includes one or more of bituminous coal, starch, aniline, polyaniline, asphalt, asphalt mesophase, phenolic resin, boron phenolic resin, sucrose, glucose, polyvinyl pyrrolidone, and tannic acid.
[0074] In some embodiments, the mass ratio of the amorphous carbon source precursor to the primary particles is 0.1 to 0.3:1.
[0075] In some embodiments, the carbon content of the second carbon coating is 0.1% to 5.0% of the mass of the secondary particle precursor.
[0076] In some embodiments, the gas-coated carbon source includes at least one of methane, ethane, ethylene, acetylene, propane, and propylene.
[0077] In some embodiments, the temperature of the vapor coating is from 600°C to 1000°C.
[0078] In some embodiments, the gas phase coating time is 0.5 h to 8.0 h.
[0079] In some embodiments, the temperature increase rate of the vapor coating is 1° C. / min to 10° C. / min.
[0080] In some embodiments, the gas phase blanketing is performed under an inert atmosphere, which includes at least one of nitrogen, argon, xenon, krypton, neon, and helium. BRIEF DESCRIPTION OF THE DRAWINGS
[0081] Figure 1 It is a schematic structural diagram of the silicon-based composite material of the present invention. DETAILED DESCRIPTION
[0082] The silicon-based composite material of the present invention can be used as a negative electrode active material in a secondary battery. The secondary battery includes a positive electrode material and a negative electrode material. The positive electrode material includes at least one of a lithium cobalt oxide positive electrode material, a lithium iron phosphate positive electrode material, a nickel cobalt manganese oxide positive electrode material, and a nickel cobalt aluminum oxide positive electrode material. The silicon-based composite material can be used alone as a negative electrode active material, or it can be mixed with other negative electrode active materials (such as natural graphite, artificial graphite, soft carbon and / or hard carbon, etc.).
[0083] The Dv50 of the silicon-based composite material is 5μm to 15μm, for example, 6μm to 10μm, and can be but not limited to 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, 11μm, 12μm, 13μm, 14μm, 15μm. Dv50 cannot be too small, otherwise it cannot form secondary particles with better performance. If it is too large, the particles contain more primary particles, and the stress on the silicon-based core when it expands is greater, and the particles are prone to breakage. The particle size span of the silicon-based composite material is N, N = (Dv90-Dv10) / Dv50. The smaller N is, the more uniform the particle size and the higher the size consistency. In order to maintain the consistency of the size of the silicon-based composite material, N is 0.9 to 1.4, and can be but not limited to 0.9, 1.0, 1.1, 1.2, 1.3, 1.4. The electrical conductivity of the silicon-based composite material is 1.0 S / cm to 3.0 S / cm, and may be, but is not limited to, 1.0 S / cm, 1.5 S / cm, 2.0 S / cm, 2.5 S / cm, and 3.0 S / cm. The specific surface area of the silicon-based composite material is 0.7 m 2 / g to 1.5m 2 / g, can be but not limited to 0.7m 2 / g, 0.8m 2 / g, 0.9m 2 / g, 1.0m 2 / g, 1.1m 2 / g, 1.2m 2 / g, 1.3m 2 / g, 1.4m 2 / g, 1.5m 2 / g. The silicon-based composite material is protected by the carbon coating outer layer and the carbon filling layer, and has a low pH, for example, 10.5 to 11.5, and can be but not limited to 10.5, 10.6, 10.7, 10.8, 10.9, 11.0, 11.1, 11.2, 11.3, 11.4, 11.5. The content of carbon element in the silicon-based composite material is 10wt.% to 30wt.%, and can be but not limited to 10wt.%, 12wt.%, 14wt.%, 16wt.%, 18wt.%, 20wt.%, 22wt.%, 24wt.%, 26wt.%, 28wt.%, 30wt.%. The content of LiOH in the silicon-based composite material is ≤0.10wt.%, and may be, but is not limited to, ≤0.10wt.%, ≤0.09wt.%, ≤0.08wt.%, ≤0.07wt.%, ≤0.06wt.%, ≤0.05wt.%, ≤0.04wt.%, ≤0.03wt.%, ≤0.02wt.%, ≤0.01wt.%. The content of Li2CO3 in the silicon-based composite material is ≤0.1wt.%, and may be, but is not limited to, ≤0.10wt.%, ≤0.09wt.%, ≤0.08wt.%, ≤0.07wt.%, ≤0.06wt.%, ≤0.05wt.%, ≤0.04wt.%, ≤0.03wt.%, ≤0.02wt.%, ≤0.01wt.%.
[0084] The first coulombic efficiency of the silicon-based composite material is ≥90.0%, and may be, but is not limited to, ≥90.0%, ≥90.5%, ≥91.0%, ≥91.5%, ≥92.0%, ≥92.5%, ≥93.0%, ≥93.5%, ≥94.0%, ≥94.5%, 95.0%. The first charging capacity of the silicon-based composite material is ≥1200mAh / g, and may be, but is not limited to, ≥1200mAh / g, ≥1210mAh / g, ≥1220mAh / g, ≥1230mAh / g, ≥1240mAh / g,
[0085] ≥1250mAh / g, ≥1260mAh / g, ≥1270mAh / g, ≥1280mAh / g, ≥1290mAh / g,
[0086] ≥1300mAh / g. The first-week reversible capacity of the silicon-based composite material is ≥459.0mAh / g, which may be, but is not limited to, ≥459.0mAh / g, ≥459.5mAh / g, ≥460.0mAh / g, ≥460.5mAh / g, ≥461.0mAh / g,
[0087] ≥461.5mAh / g, ≥462.0mAh / g, ≥462.5mAh / g, ≥463.0mAh / g. The 0.2C reversible capacity of the silicon-based composite material is ≥444.0mAh / g, and may be, but is not limited to, ≥444.0mAh / g, ≥444.5mAh / g, ≥445.0mAh / g, ≥445.5mAh / g, ≥446.0mAh / g, ≥446.5mAh / g, ≥447.0mAh / g,
[0088] ≥447.5mAh / g, ≥448.0mAh / g, ≥448.5mAh / g, ≥449.0mAh / g. The 0.2C reversible capacity retention rate of the silicon-based composite material is ≥96.0%, which may be, but is not limited to, ≥96.0%, ≥96.2%, ≥96.4%, ≥96.6%, ≥96.8%, ≥97.0%, ≥97.2%, ≥97.4%, ≥97.6%, ≥97.8%, 98.0%. The 1.0C reversible capacity of the silicon-based composite material is ≥415.0mAh / g, which may be, but is not limited to, ≥415.0mAh / g, ≥415.5mAh / g, ≥416.0mAh / g, ≥416.5mAh / g, ≥417.0mAh / g, ≥417.5mAh / g,
[0089] ≥418.0mAh / g, ≥418.5mAh / g, ≥419.0mAh / g. The 1.0C reversible capacity retention rate of the silicon-based composite material is ≥90.5%, which may be, but is not limited to, ≥90.5%, ≥90.7%, ≥90.9%, ≥91.0%, ≥91.2%,
[0090] ≥91.4%, ≥91.6%, ≥91.8%, ≥92.0%, ≥92.2%, 92.5%. The 2.0C reversible capacity of the silicon-based composite material is ≥370.0mAh / g, which can be but not limited to ≥370.0mAh / g, ≥370.5mAh / g,
[0091] ≥371.0mAh / g, ≥371.5mAh / g, ≥372.0mAh / g, ≥372.5mAh / g, ≥373.0mAh / g,
[0092] ≥373.5mAh / g, ≥374.0mAh / g, ≥374.5mAh / g, ≥375.0mAh / g, ≥375.5mAh / g,
[0093] ≥376.0mAh / g. The 2.0C reversible capacity retention rate of the silicon-based composite material is ≥80.0%, which may be, but is not limited to, ≥80.0%, ≥80.2%, ≥80.4%, ≥80.6%, ≥80.8%, ≥81.0%, ≥81.2%, ≥81.4%,
[0094] ≥81.6%, ≥81.8%, 82.0%. The 50-week reversible capacity retention rate of the silicon-based composite material is ≥91.0%, which may be, but is not limited to, ≥91.0%, ≥91.2%, ≥91.4%, ≥91.6%, ≥91.8%, ≥92.0%, ≥92.2%,
[0095] ≥92.4%, ≥92.6%, ≥92.8%, 93.0%. The full electrical expansion rate of the silicon-based composite material after 50 cycles is ≤45.0%, which can be but not limited to ≤45%, ≤44%, ≤43%, ≤42%, ≤41%, ≤40%,
[0096] ≤39%, ≤38%, ≤37%, ≤36%, ≤35%, ≤34%, ≤33%, ≤32%, ≤31%,
[0097] ≤30%.
[0098] like Figure 1 As shown, the silicon-based composite material of the present invention includes secondary particles 100. The secondary particles 100 include a carbon-coated outer layer 10, a carbon filling layer 30 and a plurality of primary particles 50. The carbon-coated outer layer 10 wraps the carbon filling layer 30. The plurality of primary particles 50 are filled in the carbon filling layer 30, and a plurality of conductive carbon particles 31 may also be filled in the carbon filling layer 30. The primary particles 50 are silicon-based material particles containing lithium silicate, including a silicon-based core 51 and a carbon-coated inner layer 53 wrapping the silicon-based core 51.
[0099] Among them, a small particle size of the primary particles is conducive to improving the rate performance, but it is easy to break and pulverize during the charge and discharge process, which affects the cycle performance; and if the particle size is too large, the diffusion distance of lithium ions in the material becomes longer, and the impedance is large, which affects the rate charge and discharge performance of the material. Therefore, the Dv50 of the primary particles is 0.5μm to 5.0μm, for example, 1.0μm to 3.0μm, and specifically can be but not limited to 0.5μm, 0.6μm, 0.8μm, 1.0μm, 2.0μm, 3.0μm, 4.0μm, 5.0μm. The silicon-based core includes lithium silicate and nano-silicon. Lithium silicate includes at least Li2SiO3, and lithium silicate can be Li2SiO3, or a mixture of Li2SiO3 and Li2SiO3. The size of nano silicon is 1nm to 20nm, and can be but not limited to 1nm, 2nm, 4nm, 6nm, 8nm, 10nm, 12nm, 14nm, 16nm, 18nm, 20nm. As an embodiment, the size of nano silicon is 2nm to 6nm. The higher the content of lithium element in the silicon-based core, the higher the first coulomb efficiency of the material, but the cost also increases, so for taking both into account, the content of lithium element in the silicon-based core is 5wt.% to 15wt.%, for example, 7wt.% to 10wt.%, and can be but not limited to 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%. The carbon-coated inner layer is obtained by gas phase coating or solid phase coating. The carbon-coated inner layer is provided to improve the surface conductivity of the silicon-based composite material and give full play to the performance of the material. Therefore, the thickness cannot be too thick or too thin. The thickness of the carbon-coated inner layer of the present invention is 20nm to 100nm, for example, 40nm to 80nm, and can be but not limited to 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm. In order to achieve effective coating of the silicon-based core, the carbon-coated inner layer accounts for 1wt.% to 10wt.% of the primary particle, for example, 2wt.% to 6wt.%, and can be but not limited to 1wt.%, 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10w.t%.
[0100] The carbon-coated outer layer is formed by gas phase coating, and the thickness of the carbon-coated outer layer is 20nm to 100nm, for example, 30nm to 70nm, and can be but not limited to 20nm, 30nm, 40nm, 50nm, 60nm, 70nm, 80nm, 90nm, 100nm. Within this thickness range, lithium ions can pass through quickly without generating electrochemical polarization.
[0101] The carbon filling layer accounts for 2wt.% to 15wt.% of the silicon-based composite material, which can be but not limited to 2wt.%, 3wt.%, 4wt.%, 5wt.%, 6wt.%, 7wt.%, 8wt.%, 9wt.%, 10wt.%, 11wt.%, 12wt.%, 13wt.%, 14wt.%, 15wt.%. The carbon filling layer is doped with conductive carbon particles to enhance the migration and diffusion of electrons within the carbon filling layer. The conductive carbon particles include at least one of graphite, conductive carbon black, acetylene black, carbon nanotubes and graphene. Since the conductive carbon particles are chemically inert, if the content is too high, it is difficult to form a continuous phase with the carbon filling layer, which can easily lead to the instability of the carbon filling layer skeleton and cause structural collapse; if the content is too low, it is easy to affect the transfer of electrons in the carbon filling layer, which has an adverse effect on the electrochemical performance. The conductive carbon particles account for 0.5wt.% to 10.0wt.% of the carbon filling layer, for example 2.0wt.% to 5.0wt.%, and can be but not limited to 0.5wt.%, 1.0wt.%, 2.0wt.%, 3.0wt.%, 4.0wt.%, 5.0wt.%, 6.0wt.%, 7.0wt.%, 8.0wt.%, 9.0wt.%, 10.0wt.%.
[0102] The minimum size of the carbon filling layer between the primary particles and the carbon-coated outer layer is D. If the D value is too small, the barrier ability to water is poor, and the lithium silicate in the inner core is easily dissolved, resulting in an increase in the pH value and residual alkali content of the system, and the risk of gas production. If the D value is too large, the content of the effective ingredient in the material is reduced, and the gram capacity of the material is low. D of the present invention is ≥ 0.5 μm, for example, 0.5 μm ≤ D ≤ 2.0 μm, or 1.0 μm ≤ D ≤ 1.5 μm, and can be but not limited to 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm, 1.9 μm, 2.0 μm. The maximum size of the carbon filling layer between the primary particles and the carbon coating outer layer is H, 0.8 μm ≤ H ≤ 1.8 μm, and can be but not limited to 0.8 μm, 0.9 μm, 1.0 μm, 1.1 μm, 1.2 μm, 1.3 μm, 1.4 μm, 1.5 μm, 1.6 μm, 1.7 μm, 1.8 μm. R = HD, R ≤ 1.0, for example, R ≤ 0.9, or R ≤ 0.8, and R can be but not limited to 1.0, 0.9, 0.8, 0.7, 0.6, 0.5.
[0103] The method for preparing the silicon-based composite material of the present invention comprises step (I), step (II) and step (III).
[0104] Step (I) of preparing primary particles comprises: xThe powder is subjected to the first carbon coating to obtain primary particle precursors. The primary particle precursors are mixed with a lithium source, sintered and then post-treated to obtain primary particles, where 0 < x < 2.
[0105] Among them, 0 < x < 2, for example, 0.5 ≤ x ≤ 1.5. x can be but is not limited to 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.0, 1.1, 1.2, 1.3, 1.4, 1.5, 1.6, 1.7. As an example, x is 1. The Dv50 of SiO x is 1 μm to 10 μm. The Dv50 can be but is not limited to 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm. The SiO x powder can be obtained by crushing, classifying, and screening massive SiO x The crushing and classification can be operated by corresponding equipment. The sieve mesh used for screening is 100 mesh to 500 mesh. As an example, the sieve mesh can be but is not limited to 100 mesh, 130 mesh, 150 mesh, 170 mesh, 200 mesh, 230 mesh, 250 mesh, 300 mesh, 350 mesh, 400 mesh, 450 mesh, 500 mesh.
[0106] The first carbon coating is a gas-phase coating or a solid-phase coating. The gas-phase coating and the solid-phase coating can be operated in a conventional manner. The carbon content of the first carbon coating is 0.5% to 5.0% of the mass of the SiO x powder, and can be but is not limited to 0.5%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%. As an example, the gas-phase coating can be but is not limited to SiO xThe powder is placed in a rotary furnace, an inert gas is introduced at a rate of 1 L / min to 10 L / min, the temperature is raised to 600°C to 1000°C at a rate of 1°C / min to 10°C / min, a gas phase organic carbon source is introduced at a rate of 0.1 L / min to 1.0 L / min for insulation reaction for 0.5 h to 8.0 h, and naturally cooled to room temperature. Wherein, the inert gas includes at least one of nitrogen, argon and helium. The introduction rate of the inert gas may be, but is not limited to, 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min. The heating rate may be, but is not limited to, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min. The reaction temperature may be, but is not limited to, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C. The gas phase organic carbon source may be, but is not limited to, at least one of methane, ethane, ethylene, acetylene, propane, and propylene. The rate of introduction of the gas phase organic carbon source may be, but is not limited to, 0.1 L / min, 0.2 L / min, 0.3 L / min, 0.4 L / min, 0.5 L / min, 0.6 / min, 0.7 L / min, 0.8 L / min, 0.9 L / min, 1.0 / min. The time of the insulation reaction may be, but is not limited to, 0.5 h, 1.0 h, 2.0 h, 3.0 h, 4.0 h, 5.0 h, 6.0 h, 7.0 h, 8.0 h. As an example, the solid phase coating may be, but is not limited to, SiO x The powder is mixed and dispersed at high speed with an organic carbon source, heated to 600°C to 1000°C at a rate of 1°C / min to 10°C / min in an inert gas environment for heat treatment, and naturally cooled to room temperature. Among them, the organic carbon source may be, but is not limited to, at least one of phenol, solid asphalt, glucose, sucrose, phenolic resin and starch. High-speed mixing and dispersion can be carried out using general equipment, and the parameters used for mixing may be conventional parameters. The heating rate may be, but is not limited to, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5L / min, 6L / min, 7L / min, 8L / min, 9L / min, 10L / min. The temperature of the heat treatment may be, but is not limited to, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C.
[0107] The lithium source includes one or more of lithium hydride, lithium hydroxide, lithium nitride, lithium amide, alkyl lithium and metallic lithium. The lithium source accounts for 5wt.% to 20wt.% of the mass of the primary particle precursor, and can be but not limited to 5wt.%, 6wt.%, 8wt.%, 10wt.%, 12wt.%, 14wt.%, 16wt.%, 18wt.%, 20wt.%. The primary particle precursor and the lithium source are sintered in a protective atmosphere after solid phase mixing, which is solid phase pre-lithium. The protective atmosphere includes one or more of nitrogen, helium, argon, neon and xenon. The sintering temperature is 500°C to 750°C, for example, 500°C to 700°C, and can be but not limited to 500°C, 550°C, 600°C, 650°C, 700°C, 750°C. The heating rate of sintering is 1°C / s to 10°C / s, for example, 4°C / s to 8°C / s, and may be, but not limited to, 1°C / s, 2°C / s, 3°C / s, 4°C / s, 5°C / s, 6°C / s, 7°C / s, 8°C / s, 9°C / s, and 10°C / s. The holding time of sintering is 4h to 24h, for example, 8h to 16h, and may be, but not limited to, 4h, 6h, 8h, 10h, 12h, 14h, 16h, 18h, 20h, 22h, and 24h.
[0108] The post-treatment includes cooling, washing and drying in sequence. After cooling to room temperature, a non-acidic solvent is used for washing to remove impurities. The non-acidic solvent includes one or more of water, weak alkaline water, alcohol, ether, ketone and benzene. The mass ratio of the non-acidic solvent to the sintered product is 1 to 5:1, which can be but not limited to 1:1, 2:1, 3:1, 4:1, 5:1. Drying can be performed by filter pressing drying or vacuum drying.
[0109] Step (II) of preparing the secondary particle precursor comprises: solid-phase mixing the primary particles, the binder and the amorphous carbon source precursor, and sieving to obtain the secondary particle precursor.
[0110] The binder includes one or more of epoxy resin, polyurethane and acrylate. The mass ratio of the binder to the primary particles is 0.005 to 0.200:1, which can be, but not limited to, 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1, 0.010:1, 0.015:1, 0.020:1, 0.030:1, 0.040:1, 0.050:1, 0.060:1, 0.070:1, 0.080:1, 0.090:1, 0.100:1, 0.150:1, 0.200:1. The amorphous carbon source precursor includes one or more of bituminous coal, starch, aniline, polyaniline, asphalt, asphalt mesophase, phenolic resin, boron phenolic resin, sucrose, glucose, polyvinyl pyrrolidone and tannic acid. The mass ratio of the amorphous carbon source precursor to the primary particles is 0.1 to 0.3:1, and may be, but not limited to, 0.10:1, 0.13:1, 0.15:1, 0.17:1, 0.20:1, 0.23:1, 0.25:1, 0.28:1, and 0.30:1. Several conductive carbon particles may be added to the solid phase mixing. The conductive carbon particles include at least one of graphite, conductive carbon black, acetylene black, carbon nanotubes, and graphene. The mass ratio of the conductive carbon particles to the primary particles is 0.001 to 0.010:1, and may be, but not limited to, 0.001:1, 0.002:1, 0.003:1, 0.004:1, 0.005:1, 0.006:1, 0.007:1, 0.008:1, 0.009:1, and 0.010:1.
[0111] The mixing and granulation process of primary particles, binder and amorphous carbon source precursor is completed in solid phase mixing. The equipment used for solid phase mixing includes a mechanical fusion machine, a VC high-speed mixer, a planetary mixer or a high shear mixer. The maximum linear velocity of the end of the equipment used for solid phase mixing is 10m / s to 20m / s, for example, 14m / s to 18m / s, which can be but not limited to 10m / s, 11m / s, 12m / s, 13m / s, 14m / s, 15m / s, 16m / s, 17m / s, 18m / s, 19m / s, 20m / s. The time of solid phase mixing is 0.5h to 4.0h, which can be but not limited to 0.5h, 1.0h, 1.5h, 2.0h, 2.5h, 3.0h, 3.5h, 4.0h.
[0112] The preparation of secondary particles in step (III) includes: subjecting the secondary particle precursor to a second carbon coating.
[0113] The temperature of the second carbon coating is not lower than the carbonization temperature of the binder and the amorphous carbon source precursor. Therefore, during the second carbon coating process, the binder and the amorphous carbon precursor decompose into amorphous carbon, and the amorphous carbon constitutes a carbon filling layer, or the amorphous carbon and conductive carbon particles constitute a carbon filling layer.
[0114] The second carbon coating is gas-phase coating, which may be, but is not limited to, placing the secondary particle precursor in a rotary kiln, introducing an inert gas at a rate of 1 L / min to 10 L / min, heating to 600°C to 1000°C at a rate of 1°C / min to 10°C / min, introducing a gaseous organic carbon source at a rate of 0.1 L / min to 1.0 L / min for insulation reaction for 0.5 h to 8.0 h, and naturally cooling to room temperature. Wherein, the inert gas includes at least one of nitrogen, argon and helium. The introduction rate of the inert gas may be, but is not limited to, 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min. The heating rate may be, but is not limited to, 1°C / min, 2°C / min, 3°C / min, 4°C / min, 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min. The reaction temperature may be, but is not limited to, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C. The gas phase organic carbon source may be, but is not limited to, at least one of methane, ethane, ethylene, acetylene, propane and propylene. The introduction rate of the gas phase organic carbon source may be, but is not limited to, 0.1L / min, 0.2L / min, 0.3L / min, 0.4L / min, 0.5L / min, 0.6 / min, 0.7L / min, 0.8L / min, 0.9L / min, 1.0 / min. The time of the heat preservation reaction may be, but is not limited to, 0.5h, 1.0h, 2.0h, 3.0h, 4.0h, 5.0h, 6.0h, 7.0h, 8.0h. The carbon content of the second carbon coating is 0.1% to 5.0% of the mass of the secondary particle precursor, and may be, but is not limited to, 0.1%, 0.3%, 0.5%, 0.8%, 1.0%, 1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%.
[0115] In order to better illustrate the purpose, technical scheme and beneficial effects of the present invention, the present invention will be further described below in conjunction with specific embodiments. It should be noted that the following implementation method is a further explanation of the present invention and should not be used as a limitation of the present invention.
[0116] Example 1
[0117] This embodiment is a method for preparing a silicon-based composite material, which includes the following steps.
[0118] (I) Preparation of primary particles
[0119] The blocky silicon oxide is crushed, graded and sieved to obtain a micron silicon oxide powder with a Dv50 of 2μm, which is placed in a rotary kiln, nitrogen is introduced as a protective atmosphere, the temperature is raised to 700°C, methane is introduced as a gas source, and the temperature is kept for 6 hours, and carbon is coated to obtain a primary particle precursor with a carbon content of 3.0wt%. 1000g of the primary particle precursor is mixed with 130g of lithium nitride for VC, placed in a nitrogen protective atmosphere, heated to 750°C at a rate of 6°C / s, sintered and kept for 6 hours, and washed and impurities are removed with water (the mass ratio of the sintered product to water is 1:3) as a solvent after cooling, and the primary particles are obtained after filter pressing and drying.
[0120] (II) Preparation of secondary particle precursor
[0121] 1000g of primary particles, 20g of epoxy resin, 300g of asphalt and 5g of conductive carbon black were put into a mechanical fusion machine for heating and fusion. The maximum linear speed at the end of the mechanical fusion machine was 15m / s, the mixing time was 1h, and the output material was sieved through a 400-mesh sieve to obtain a secondary particle precursor.
[0122] (III) Preparation of secondary particles
[0123] Take 1000g of secondary particle precursor and place it in a rotary furnace. Introduce nitrogen as a protective atmosphere, raise the temperature to 700℃ at a rate of 5℃ / min, introduce methane as a gas source, and keep warm for 6 hours to carbonize and carbon-coate it. The carbon content of the carbon coating is 2.0wt.% of the secondary particle precursor. After discharging, pass through a 400-mesh sieve to obtain secondary particles.
[0124] The obtained silicon-based composite material was tested by XRD and EDS, and it was found that the secondary particles included a carbon-coated outer layer, a carbon filling layer and a plurality of primary particles. The thickness of the carbon-coated outer layer was 40nm and wrapped the carbon filling layer. A plurality of primary particles and conductive carbon black particles were filled in the carbon filling layer. The primary particles included a silicon-based core and a carbon-coated inner layer that wrapped the silicon-based core. The silicon-based core included Li2SiO3, Li2Si2O5 and nano-silicon. The size of the nano-silicon was 5nm, and the thickness of the carbon-coated inner layer was 50nm.
[0125] Example 2
[0126] The difference between Example 2 and Example 1 is that the micron silicon dioxide powder Dv50 is replaced with 3 μm.
[0127] Example 3
[0128] The difference between Example 3 and Example 1 is that the amorphous carbon source precursor is replaced with boron phenolic resin (FB).
[0129] Example 4
[0130] The difference between Example 4 and Example 1 is that the binder is replaced by acrylate, and the conductive carbon particles are replaced by carbon nanotubes.
[0131] Example 5
[0132] The difference between Example 5 and Example 1 is that the lithium source is replaced with 180 g of lithium hydroxide.
[0133] Example 6
[0134] The difference between Example 6 and Example 1 is that the added amount of epoxy resin is 100g, the added amount of asphalt is 150g, the added amount of conductive carbon black is 10g, and the equipment used for solid phase mixing is a VC high-speed mixer.
[0135] Example 7
[0136] The difference between Example 7 and Example 1 is that the maximum linear velocity at the end of the equipment used for solid phase mixing is 18 m / s, and the solid phase mixing time is 0.5 h.
[0137] Example 8
[0138] The difference between Example 8 and Example 1 is that no conductive carbon black is added when preparing the secondary particle precursor.
[0139] Example 9
[0140] The difference between Example 9 and Example 1 is that when preparing the primary particle precursor, the micron silicon oxide powder and solid asphalt are mixed and dispersed at a high speed, the temperature is raised to 800°C at a rate of 5°C / min in an argon environment for heat treatment, and naturally cooled to room temperature to obtain a primary particle precursor with a carbon content of 2.0wt%.
[0141] The remaining steps are the same as in Example 1.
[0142] Example 10
[0143] The difference between Example 10 and Example 1 is that in the preparation of the primary particles in step (I), the sintering temperature is 650° C., the heating rate is 5° C. / s, and the holding time is 20 h.
[0144] Embodiment 11
[0145] The difference between Example 11 and Example 1 is that the preparation of secondary particles in step (III) is as follows: 1000 g of secondary particle precursor is placed in a rotary furnace, argon gas is introduced as a protective atmosphere, the temperature is raised to 900°C at a rate of 8°C / min, ethylene is introduced as a gas source, and the temperature is kept for 4 hours. Carbonization and carbon coating are performed, and the carbon content of the carbon coating is 2.5wt.% of the secondary particle precursor. After discharging, the material is sieved through a 400-mesh sieve to obtain secondary particles.
[0146] Comparative Example 1
[0147] The difference between Comparative Example 1 and Example 1 is that the solid phase mixing time in the preparation of the secondary particle precursor in step (II) is 6.0 h.
[0148] Comparative Example 2
[0149] The difference between Comparative Example 2 and Example 1 is that the maximum linear velocity at the end of the equipment used for solid phase mixing in the preparation of the secondary particle precursor in step (II) is 8 m / s.
[0150] Comparative Example 3
[0151] This comparative example is a method for preparing a silicon-based composite material, which includes the following steps.
[0152] (I) Preparation of Precursor
[0153] The blocky silicon oxide was crushed, graded and sieved to obtain a micron silicon oxide powder with a Dv50 of 5.7 μm, which was placed in a rotary kiln, nitrogen was introduced as a protective atmosphere, the temperature was raised to 700°C, methane was introduced as a gas source, and the temperature was kept for 6 hours, and the first carbon coating was performed to obtain a silicon oxide-based material with a carbon content of 3.0 wt%. 1000 g of silicon oxide-based material was mixed with 130 g of lithium nitride for VC, placed in a nitrogen protective atmosphere, heated to 750°C at a rate of 6°C / s, sintered and kept for 6 hours, and washed and impurities were removed using water (the mass ratio of sintered product to water was 1:3) as a solvent after cooling, and the precursor was obtained after filter pressing and drying.
[0154] (II) Second carbon coating
[0155] Take 1000g of the precursor and place it in a rotary furnace. Introduce nitrogen as a protective atmosphere, raise the temperature to 700℃ at a rate of 5℃ / min, introduce methane as a gas source, and keep warm for 6 hours to carbonize and carbon-coate it. The carbon content of the second carbon coating is 2.0wt.% of the secondary particle precursor. After discharging, pass through a 400-mesh sieve to obtain secondary particles.
[0156] Comparative Example 4
[0157] This comparative example is a method for preparing a silicon-based composite material, which includes the following steps.
[0158] (I) Preparation of Precursor
[0159] The blocky silicon oxide was crushed, graded and sieved to obtain a micron silicon oxide powder with a Dv50 of 5.7 μm, which was placed in a rotary kiln, nitrogen was introduced as a protective atmosphere, the temperature was raised to 700°C, methane was introduced as a gas source, and the temperature was kept for 6 hours, and carbon-coated to obtain a silicon oxide-based material with a carbon content of 3.0 wt%. 1000 g of silicon oxide-based material was mixed with 130 g of lithium nitride for VC, placed in a nitrogen protective atmosphere, heated to 750°C at a rate of 6°C / s, sintered and kept for 6 hours, and washed and impurities were removed using water (the mass ratio of sintered product to water was 1:3) as a solvent after cooling, and the precursor was obtained after filter pressing and drying.
[0160] (II) Second carbon coating
[0161] 1000g of precursor, 20g of epoxy resin and 300g of asphalt were put into a mechanical fusion machine for heating and fusion. The maximum linear speed at the end of the mechanical fusion machine was 15m / s and the mixing time was 1h. The material was sieved through a 400-mesh sieve and then placed in a rotary furnace. Nitrogen was introduced as a protective atmosphere and the temperature was raised to 700℃ at a rate of 5℃ / min and kept for 6h for carbonization.
[0162] Comparative Example 5
[0163] This comparative example is a method for preparing a silicon-based composite material, which includes the following steps.
[0164] (I) Preparation of primary particles
[0165] Nano-silicon with a Dv50 of 50 nm was placed in a rotary kiln, nitrogen was introduced as a protective atmosphere, the temperature was raised to 700° C., methane was introduced as a gas source, and the temperature was kept for 6 hours. It was carbon-coated to obtain primary particles with a carbon content of 5.0 wt%.
[0166] (II) Preparation of secondary particle precursor
[0167] 1000g of primary particles, 50g of epoxy resin, 1000g of asphalt and 50g of conductive carbon black were put into a mechanical fusion machine for heating and fusion. The maximum linear speed at the end of the mechanical fusion machine was 15m / s, the mixing time was 1h, and the output material was sieved through a 400-mesh sieve to obtain a secondary particle precursor.
[0168] (III) Preparation of secondary particles
[0169] Take 1000g of secondary particle precursor and place it in a rotary furnace. Introduce nitrogen as a protective atmosphere, raise the temperature to 700℃ at a rate of 5℃ / min, introduce methane as a gas source, and keep warm for 6 hours to carbonize and carbon-coate it. The carbon content of the carbon coating is 2.0wt.% of the secondary particle precursor. After discharging, pass through a 400-mesh sieve to obtain secondary particles.
[0170] Comparative Example 6
[0171] This comparative example is a method for preparing a silicon-based composite material, which includes the following steps.
[0172] (I) Preparation of primary particles
[0173] The blocky silicon oxide is crushed, graded and sieved to obtain a micron silicon oxide powder with a Dv50 of 2μm, which is placed in a rotary kiln, nitrogen is introduced as a protective atmosphere, the temperature is raised to 700°C, methane is introduced as a gas source, and the temperature is kept for 6 hours, and carbon is coated to obtain a primary particle precursor with a carbon content of 3.0wt%. 1000g of the primary particle precursor is mixed with 130g of lithium nitride for VC, placed in a nitrogen protective atmosphere, heated to 750°C at a rate of 6°C / s, sintered and kept for 6 hours, and washed and impurities are removed with water (the mass ratio of the sintered product to water is 1:3) as a solvent after cooling, and the primary particles are obtained after filter pressing and drying.
[0174] (II) Preparation of secondary particle precursor
[0175] 1000g of primary particles, 20g of epoxy resin, 300g of asphalt and 5g of conductive carbon black were put into a mechanical fusion machine for heating and fusion. The maximum linear speed at the end of the mechanical fusion machine was 15m / s, the mixing time was 1h, and the output material was sieved through a 400-mesh sieve to obtain a secondary particle precursor.
[0176] (III) Preparation of secondary particles
[0177] Take 1000g of secondary particle precursor and 20g of solid asphalt and put them in a VC mixer for high-speed dispersion and uniform mixing. Then put them in a rotary furnace and heat treat them at a rate of 5℃ / min to 800℃ in an argon environment. After discharging, pass through a 400-mesh sieve to obtain secondary particles.
[0178] The physical properties and chemical composition of the silicon-based composite materials prepared in Examples 1 to 11 and Comparative Examples 1 to 6 were tested under the following test conditions. The results are shown in Tables 1 and 2.
[0179] The silicon-based composite materials prepared in Examples 1 to 11 and Comparative Examples 1 to 6 were subjected to slurry processing performance tests under the following test conditions. The results are shown in Table 2.
[0180] The silicon-based composite materials prepared in Examples 1 to 11 and Comparative Examples 1 to 6 were respectively made into button cells for electrochemical performance testing. The button cell preparation process and test conditions are as follows. The test results are shown in Tables 3 and 4.
[0181] The test conditions are described below.
[0182] (1) Physical properties
[0183] The particle size distribution of silicon-based composites was tested using a laser particle size analyzer.
[0184] The specific surface area of silicon-based composite materials was tested using nitrogen isothermal adsorption-desorption curves.
[0185] The conductivity of silicon-based composite materials was tested using a conductivity meter.
[0186] The silicon-based composite materials prepared in Examples 1 to 11 and Comparative Examples 1 to 6 were respectively prepared into aqueous solutions, and the pH values were tested using a pH meter.
[0187] The silicon-based composite materials prepared in Examples 1 to 11 and Comparative Examples 1 to 6 were uniformly mixed with an aqueous dispersion of a binder acrylonitrile multipolymer (LA132, solid content 15%) and coated on the surface of a silicon wafer. The cross-section of the material was then obtained by plasma cutting and observed under a scanning electron microscope to determine the value of the minimum size D of the carbon filling layer.
[0188] (2) Chemical composition test
[0189] The carbon content was tested using a carbon-sulfur analyzer.
[0190] Inductively coupled plasma atomic emission spectrometry was used to test the lithium content.
[0191] Weigh 2.5 g of the silicon-based composite materials obtained in Examples 1 to 11 and Comparative Examples 1 to 6 respectively into a clean beaker, add 50 mL of pure water using a measuring cylinder, stir magnetically for 5 min at 800 rpm, filter, transfer 25 mL of the filtrate to a 150 mL beaker, then add pure water to the beaker to about 100 mL, and finally use a potentiometric titrator to titrate in DET-PH mode to test the Li2CO3 and LiOH contents.
[0192] (3) Electrochemical performance test
[0193] First charge and discharge performance test: The silicon-based composite materials prepared in Examples 1 to 11 and Comparative Examples 1 to 6 were used as active materials, respectively, and mixed with a binder polyvinylidene fluoride and a conductive agent (Super-P) in a mass ratio of 70:15:15, and an appropriate amount of N-methylpyrrolidone (NMP) was added as a solvent to prepare a slurry, which was coated on a copper foil, and vacuum dried and rolled to prepare a negative electrode sheet. A metal lithium sheet was used as a counter electrode, 1 mol / L LiPF6 and a three-component mixed solvent of EC:DMC:EMC=1:1:1 (v / v / v) were used to form an electrolyte, a polypropylene microporous membrane was used as a diaphragm, and a CR2032 button cell was assembled in a glove box filled with inert gas. The charge and discharge test of the button cell was carried out on the LANHE battery test system of Landian Electronics Co., Ltd. At room temperature, the battery is discharged at a constant current of 0.1C to a voltage of 0.01V, then discharged at a constant current of 0.02C to a voltage of 0.005V, and charged at a constant current of 0.1C to a voltage of 1.5V. The capacity charged to 1.5V is the first charging capacity, and the ratio of the first charging capacity to the first discharging capacity is the first coulombic efficiency.
[0194] Cyclic performance test: The silicon-based composite materials obtained in Examples 1 to 11 and Comparative Examples 1 to 4 and Comparative Example 6 were mixed with graphite at a mass ratio of 0.15:0.85 and used as active materials (the silicon-based composite materials obtained in Comparative Example 5 were mixed with graphite at a mass ratio of 0.05:095), mixed with a water dispersion of a binder acrylonitrile multi-polymer (LA132, solid content 15%) and a conductive agent (Super P) at a mass ratio of 70:10:20, added with an appropriate amount of water as a solvent to form a slurry, coated on a copper foil, and vacuum dried and rolled to prepare a negative electrode sheet. Metal lithium was used as the counter electrode, an electrolyte mixed with a 1 mol / L LiPF6 three-component mixed solvent at EC:DMC:EMC=1:1:1 (volume ratio) was used, and a polypropylene microporous membrane was used as a diaphragm to assemble a CR2032 button cell in a glove box filled with inert gas. The charge and discharge test of button cells was conducted on the battery test system of Blue Electric Electronics Co., Ltd. at room temperature, with a constant current of 0.2C and a charge and discharge voltage limit of 0.005 to 1.5 V. After 50 cycles, the thickness of the negative electrode at the beginning and after 50 cycles was tested, and the expansion rate of the full charge after 50 cycles and the reversible capacity retention rate after 50 cycles were calculated.
[0195] Rate performance test: The silicon-based composite materials obtained in Examples 1 to 11 and Comparative Examples 1 to 4 and Comparative Example 6 were mixed with graphite at a mass ratio of 0.15:0.85 and used as active materials (the silicon-based composite materials obtained in Comparative Example 5 were mixed with graphite at a mass ratio of 0.05:095), mixed with a water dispersion of a binder acrylonitrile multipolymer (LA132, solid content 15%) and a conductive agent (Super-P) at a mass ratio of 70:10:20, added with an appropriate amount of water as a solvent to form a slurry, coated on a copper foil, and vacuum dried and rolled to prepare a negative electrode sheet. Metal lithium was used as the counter electrode, 1 mol / L LiPF6 and a three-component mixed solvent of EC:DMC:EMC=1:1:1 (v / v) were used to form an electrolyte, a polypropylene microporous membrane was used as a diaphragm, and a CR2032 button cell was assembled in a glove box filled with inert gas. The charge and discharge test of button cells was carried out on the battery test system of Wuhan Blue Electric Electronics Co., Ltd. After 1 week of 0.1C charging and 0.2C discharging cycles, constant current and constant voltage charging was carried out at different rates of 0.2C / 1.0C / 2.0C (cutoff condition was 0.01C), followed by 0.2C constant current discharge, and the reversible capacity at different rates was recorded and compared with the reversible capacity at 0.2C to obtain the reversible capacity retention rate at different rates.
[0196] (4) Slurry processing performance test
[0197] Take 5 ml of the slurry prepared in step (3) and place it in a 20 ml syringe. Use hot melt adhesive to seal the front end of the syringe. After sealing the syringe containing the slurry, place it in a room temperature and 45°C oven for storage. Observe the movement of the syringe and observe and record it every 12 hours. Among them, "no gas production within 168 hours" means that the material does not produce gas within 168 hours under 45°C storage conditions, and subsequent observation is stopped. It does not mean that it produces gas after more than 168 hours; "gas production within 24 hours" means that gas production is found during the second observation, and the actual gas production time is between 12 hours and 24 hours.
[0198] Table 1 Test results of physical properties and chemical composition of various silicon-based composite materials
[0199]
[0200] Table 2 Test results of physical properties and chemical composition of various silicon-based composite materials
[0201]
[0202]
[0203] Table 3 Test results of the first charge-discharge performance and cycle performance of each silicon-based composite material
[0204]
[0205] Table 4 Test results of the first charge-discharge performance and cycle performance of each silicon-based composite material
[0206]
[0207]
[0208] From the results in Table 1, it can be seen that the particle size distribution of the silicon-based composite materials obtained in Examples 1 to 11 of the present invention is relatively uniform, with a certain particle size and specific surface area, high conductivity, and a certain content of carbon and lithium elements. In addition, the minimum size D of the carbon filling layer between the primary particles and the carbon-coated outer layer is ≥0.5 μm, and the size difference R ≤1.0, indicating that the formed carbon filling layer is thicker and more uniform, so the waterproof penetration ability of the material is stronger, and thus the pH value of the silicon-based composite material obtained is lower (10.5 to 11.5), the residual alkali content is low (LiOH content ≤0.1wt.%, Li2CO3 content ≤0.1wt.%), and no gas is produced after 168 hours. Therefore, the electrochemical performance of the silicon-based composite materials obtained in Examples 1 to 11 of the present invention is better. Combining the results of Table 3 and Table 4, it can be seen that the first coulombic efficiency of the silicon-based composite material is ≥90.0%, the first charging capacity is ≥1200mAh / g, the first week reversible capacity is ≥459.0mAh / g, the 0.2C reversible capacity is ≥444.0mAh / g, the 0.2C reversible capacity retention rate is ≥96.0%, the 1.0C reversible capacity is ≥415.0mAh / g, the 1.0C reversible capacity retention rate is ≥90.5%, the 2.0C reversible capacity is ≥370.0mAh / g, the 2.0C reversible capacity retention rate is ≥80.0%, the 50-week reversible capacity retention rate is ≥91.0%, and the full-charge expansion rate after 50 cycles is ≤45.0%.
[0209] By comparing Example 1 and Example 8, it can be seen that the material prepared by adding conductive carbon particles during solid phase mixing has better performance.
[0210] The mixing time of Comparative Example 1 is 6 hours. When a sufficient linear speed is obtained, the surface of the silicon-based composite material that has been mixed and granulated is continuously sheared due to long mixing, and the amorphous carbon source precursor is peeled off by a large shear force, and its D value is only 0.38 μm, so the processing performance is poor, and the pH value and residual alkali content are increased. However, it still has a granulation effect, so it has certain circulation and rate performance.
[0211] The maximum linear velocity at the end of Comparative Example 2 is 8 m / s. The shear force brought by this linear velocity cannot resist the bonding force between the binders, so the agglomeration between the materials is very obvious, the particle size is very large, the mixing is very uneven, and its D value is only 0.26 μm, so the processing performance is poor. Its particle size span N is 1.53, indicating that its particle size distribution is too wide. Compared with the silicon-based composite material obtained with a maximum linear velocity of 10 m / s to 20 m / s at the end, its material performance is not good.
[0212] Comparative Examples 3 and 4 use traditional large-particle silicon-based materials for single gas phase coating or solid phase coating, which is difficult to achieve good waterproof penetration ability. The gas phase coating thickness of Comparative Example 3 is difficult to increase, and the D value is only 0.05. The solid phase coating uniformity of Comparative Example 4 is not good and the particle size is too large, which easily causes particle agglomeration. Therefore, the processing performance of the silicon-based composite materials obtained in Comparative Examples 3 and 4 is poor, and the silicon-based negative electrode materials all produce gas within 24 hours. Moreover, after a single particle is coated, the lithium ion migration channel is insufficient, and the rate performance of the material is affected. As shown in Table 2, at high rates, its rate reversible capacity retention rate is far inferior to that of Examples 1 to 11.
[0213] In Comparative Example 5, nano silicon is used as the primary particle. Since nano silicon has poor conductivity and large specific surface area, the addition amount of the binder, amorphous carbon source precursor and conductive carbon particles need to be increased, otherwise the normal performance will not be achieved. Under the same solid phase mixing granulation and sintering process, the particle size span is large during the granulation process. In addition, the expansion of nano silicon is large, and the expansion rate of the obtained silicon-based composite material is high, resulting in poor cycle and rate performance.
[0214] In Comparative Example 6, solid phase coating was used for the second carbon coating, and the D value of the obtained material was only 0.10 μm, while the H value was 1.78 μm and the R value was as high as 1.68 μm, indicating that a uniform and thick carbon filling layer could not be formed. This is mainly because when solid phase coating is used, a higher mixing line speed is required for uniform mixing, which leads to the destruction of the original secondary structure and a small D value. Therefore, even if secondary particles are made, the performance improvement is still limited.
[0215] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention is described in detail with reference to the preferred embodiments, it is not limited to those listed in the embodiments. Those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A method for preparing a silicon-based composite material, characterized in that: Includes steps: (I) Preparation of primary particles SiO x The powder is firstly carbon coated to obtain a primary particle precursor, the primary particle precursor is mixed with a lithium source, sintered and then post-processed to obtain a primary particle, <x<2; (II) Preparation of secondary particle precursor The primary particles, the binder and the amorphous carbon source precursor are solid-phase mixed and sieved to obtain a secondary particle precursor, wherein the maximum linear speed of the end of the equipment used for the solid-phase mixing is 10 m / s to 20 m / s, and the solid-phase mixing time is 0.5 h to 4.0 h; (III) Preparation of secondary particles The secondary particle precursor is subjected to a second carbon coating, wherein the second carbon coating is gas phase coating, and the temperature of the second carbon coating is not lower than the carbonization temperature of the binder and the amorphous carbon source precursor.
2. The method for preparing the silicon-based composite material according to claim 1, characterized in that: A plurality of conductive carbon particles are added into the solid phase mixture.
3. The method for preparing the silicon-based composite material according to claim 2, characterized in that: The conductive carbon particles include at least one of graphite, conductive carbon black, acetylene black, carbon nanotubes and graphene, and the mass ratio of the conductive carbon particles to the primary particles is 0.001 to 0.010:
1.
4. The method for preparing the silicon-based composite material according to claim 1, characterized in that: Contains at least one of the following features (1) to (22): (I) SiO x Powder block SiO x Crushing, grading and screening are available; (ii) SiO x Powder Dv50 is 1μm to 10μm; (iii) the first carbon coating is gas phase coating or solid phase coating; (IV) The carbon content of the first carbon coating is SiO x 0.5% to 5.0% of powder mass; (5) the primary particle precursor and the lithium source are mixed in a solid phase and then sintered in a protective atmosphere; (vi) the post-treatment includes cooling, washing and drying in sequence; (VII) The lithium source comprises one or more of lithium hydride, lithium hydroxide, lithium nitride, lithium amide, alkyl lithium and metallic lithium; (VIII) the lithium source accounts for 5wt.% to 20wt.% of the mass of the primary particle precursor; (IX) The sintering temperature is 500°C to 750°C; (10) The heating rate of the sintering is 1°C / s to 10°C / s; (XI) The sintering holding time is 4h to 24h; (XII) The equipment used for solid phase mixing includes a mechanical fusion machine, a VC high-speed mixer, a planetary mixer or a high shear mixer; (XIII) The adhesive comprises one or more of epoxy resin, polyurethane and acrylate; (XIV) The mass ratio of the binder to the primary particles is 0.005 to 0.200:1; (XV) The amorphous carbon source precursor includes one or more of bituminous coal, starch, aniline, polyaniline, asphalt, asphalt mesophase, phenolic resin, boron phenolic resin, sucrose, glucose, polyvinyl pyrrolidone and tannic acid; (XVI) The mass ratio of the amorphous carbon source precursor to the primary particles is 0.1 to 0.3:1; (XVII) The carbon content of the second carbon coating is 0.1% to 5.0% of the mass of the secondary particle precursor; (XVIII) The gas-coated carbon source comprises at least one of methane, ethane, ethylene, acetylene, propane and propylene; (19) The temperature of the gas phase coating is 600°C to 1000°C; (XX) The gas phase coating time is 0.5h to 8.0h; (XXI) The heating rate of the gas phase coating is 1°C / min to 10°C / min; (XXII) The gas phase coating is carried out under an inert atmosphere, and the inert atmosphere includes at least one of nitrogen, argon, xenon, krypton, neon and helium.
5. The silicon-based composite material prepared by the method for preparing a silicon-based composite material according to any one of claims 1 to 4, characterized in that: The invention comprises secondary particles, wherein the secondary particles comprise a carbon coating outer layer, a carbon filling layer and a plurality of primary particles, wherein the carbon coating outer layer wraps the carbon filling layer, and the plurality of primary particles are filled in the carbon filling layer, and the primary particles are silicon-based material particles containing lithium silicate, and the minimum size of the carbon filling layer between the primary particles and the carbon coating outer layer is D, and D≥0.5 μm.
6. The silicon-based composite material according to claim 5, characterized in that: The silicon-based material particles include a silicon-based core and a carbon-coated inner layer wrapping the silicon-based core, and the silicon-based core includes lithium silicate and nano-silicon.
7. The silicon-based composite material according to claim 6, characterized in that: Contains at least one of the following features ① to ⑤: ① The lithium silicate comprises at least Li2SiO3; ② The content of lithium in the silicon-based core is 5wt.% to 15wt.%; ③ The size of the nano-silicon is 1nm to 20nm; ④ The thickness of the carbon coating inner layer is 20nm to 100nm; ⑤ The carbon-coated inner layer accounts for 1wt.% to 10wt.% of the primary particles.
8. The silicon-based composite material according to claim 5, characterized in that: The carbon filling layer is also filled with a plurality of conductive carbon particles.
9. The silicon-based composite material according to claim 8, characterized in that: The conductive carbon particles account for 0.5 wt. % to 10.0 wt. % of the carbon filling layer.
10. The silicon-based composite material according to claim 5, characterized in that: Contains at least one of the following features (1) to (25): (1) The Dv50 of the silicon-based composite material is 5 μm to 15 μm; (2) The particle size span of the silicon-based composite material is N, N = (Dv90-Dv10) / Dv50, N is 0.9 to 1.4; (3) The electrical conductivity of the silicon-based composite material is 1.0 S / cm to 3.0 S / cm; (4) The specific surface area of the silicon-based composite material is 0.7 m 2 / g to 1.5m 2 / g; (5) The pH value of the silicon-based composite material is 10.5 to 11.5; (6) The first coulombic efficiency of the silicon-based composite material is ≥ 90.0%; (7) The initial charging capacity of the silicon-based composite material is ≥1200 mAh / g; (8) The first-week reversible capacity of the silicon-based composite material is ≥459.0 mAh / g; (9) The 0.2C reversible capacity of the silicon-based composite material is ≥ 444.0 mAh / g; (10) The 0.2C reversible capacity retention rate of the silicon-based composite material is ≥ 96.0%; (11) The 1.0C reversible capacity of the silicon-based composite material is ≥415.0 mAh / g; (12) The 1.0C reversible capacity retention rate of the silicon-based composite material is ≥ 90.5%; (13) The 2.0C reversible capacity of the silicon-based composite material is ≥370.0 mAh / g; (14) The 2.0C reversible capacity retention rate of the silicon-based composite material is ≥80.0%; (15) The 50-week reversible capacity retention rate of the silicon-based composite material is ≥ 91.0%; (16) The full electrical expansion rate of the silicon-based composite material after 50 cycles is ≤45.0%; (17) The carbon content in the silicon-based composite material is 10wt.% to 30wt.%; (18) The content of LiOH in the silicon-based composite material is ≤0.1wt.%; (19) The content of Li2CO3 in the silicon-based composite material is ≤0.1wt.%; (20) The thickness of the carbon coating outer layer is 20 nm to 100 nm; (21) The Dv50 of the primary particles is 0.5 μm to 5.0 μm; (22) The carbon filling layer accounts for 2wt.% to 15wt.% of the silicon-based composite material; (23) 0.5 μm ≤ D ≤ 2.0 μm; (24) The maximum size of the carbon filling layer between the primary particles and the carbon coating outer layer is H, 0.8 μm ≤ H ≤ 1.8 μm; (25) The maximum size of the carbon filling layer between the primary particles and the carbon coating outer layer is H, R = HD, R ≤ 1.0.
Citation Information
Patent Citations
Negative electrode material and preparation method thereof, electrode and secondary battery
CN112467097A
High-first-effect and high-magnification silicon-based negative electrode material and preparation method thereof
CN113422013A
Silicon-carbon composite material, preparation method of silicon-carbon composite material and secondary battery
CN116230905A
High-stability silicon-based negative electrode material and preparation method and application thereof
CN116504955A